The last neanderthal ebook A novel. - Cameron, Claire (2017)
From the author of The Bear , the enthralling story of two women separated by millennia, but linked by an epic journey that will transform them both. Forty thousand years in the past, the last family of Neanderthals roams the earth. After a crushingly hard winter, their numbers are low, but Girl, the oldest daughter, is just coming of age and her family is determined to travel to the annual meeting place and find her a mate. But the unforgiving landscape takes its toll, and Girl is left alone to care for Runt, a foundling of unknown origin. As Girl and Runt face the coming winter storms, Girl realizes she has one final chance to save her people, even if it means sacrificing part of herself. In the modern day, archaeologist Rosamund Gale works well into her pregnancy, racing to excavate newly found Neanderthal artifacts before her baby comes. Linked across the ages by the shared experience of early motherhood, both stories examine the often taboo corners of women's lives. Haunting, suspenseful, and profoundly moving, The Last Neanderthal asks us to reconsider all we think we know about what it means to be human.